Kompetensi Sosial Pendidik dan Pengasuh dalam Membangun Keunggulan Taruna di Politeknik Penerbangan Makassar - Bahrawi, Ahmad; Idyaningsih, Nining (Politeknik Penerbangan Makassar, 2020)
This study aims to describe the social competence of educators and tutors in building cadet excellence in the makassar aviation polytechnic. This research is qualitative research with a case study approach. Data collection techniques used are interviews, observations, and documentation. The data obtained is then analyzed using qualitative descriptive analysis techniques conducted interactively. The results of this study are: the social competence of educators and tutors is realized in three forms, namely cooperation, participation, and sensitivity. The social competence of educators and tutors are the existence of good cooperation and coordination between each other and to the leadership. Furthermore, educators and caregivers actively participate by directly fostering and developing Cadets both academically and non-academically. The sensitivity and care of educators and tutors is evidenced by differences in parenting patterns, variations in learning methods, individual tasks, and objective and non-discriminatory assessments.